First Principles Study of the Ambipolarity in a Germanene Nanoribbon Tunneling Field Effect Transistor. (25th November 2019) - Samipour, Azam; Dideban, Daryoosh; Heidari, Hadi
Abstract : In this article, the effects of hetero-dielectric gate material and gate-drain underlap on the ambipolar and ON-state current of a germanene nanoribbon (GeNR) tunneling field-effect transistors (TFETs) is examined. The simulations are performed using the combination of density functional theory (DFT) and non-equilibrium Green's function (NEGF) formalism. It was observed that using high-k dielectric gate material increases the ON-state current while the combination of hetero-dielectric gate material and gate-drain underlap suppresses the ambipolar current and improves the ON-state current. In addition, the effect of various hetero-junctions in the source region on the performance of GeNR-TFET was investigated. Due to the dependency between the width and energy bandgap in GeNR, utilizing a small bandgap in the source improves ON-state current and its ambipolar behavior.